An Evolutionary Algorithm and discrete event simulation for optimizing inspection strategies for multi-stage processes - Van Volsem, Sofie; Dullaert, Wout; Van Landeghem, Hendrik (European journal of operational research, 2007)
The problem of determining the optimal inspection strategy for a given multi-stage production process, i.e. the inspection strategy that results in the lowest total inspection cost, while still assuring a required output quality, is modelled as a joint optimization of inspection location, type and inspection limits. A fusion between a discrete event simulation to model the multi-stage process subject to inspection and to calculate the resulting inspection costs, and an Evolutionary Algorithm (EA) to optimize the inspection strategies, is suggested.